Perbanyakan Vegetatif Tanaman Jarak Pagar (Jatropha curcas L.) dengan Stek Batang: Pengaruh Panjang dan Diameter Stek - Bambang Budi Santoso; , Hasnam; , Hariyadi; Slamet Susanto; Bambang Sapta Purwoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
Since physic nut (Jatropha curcas L.) is heterozygous, sexual propagation results in great genotypic and phenotypic variability. Development of efficient techniques for asexual propagation would benefit the nursery industry as this would lead to selection and production of particular clones with desirable characteristics. Therefore, two following studies were conducted from September until December 2007. The objective was develop a protocol for vegetative propagation of physic nut by stem cutting in different size of cutting. The first experiment was dealt with stem cutting length (20 cm, 25 cm, and 30 cm) at the same size of diameter (2.5-3.0 cm), and the second experiment was dealt with diameter of stem cutting (3 cm, 2.5-2.9 cm, 2.0-2.4 cm, and 1.5-1.9 cm) at the same size of length (30 cm). Each of experiment was designed in Completely Randomized Design with three replications. Each experimental unit consisted of 25 seedlings. The result showed that cutting growth varied depending on length and diameter of stem cutting. However, better seedling growth and better survival of young plant of physic nut can be obtained from stem cutting with 20-30 cm in length and stem cutting with 2.0-2.9 cm in diameter. Key words: cutting diameter, cutting length, Jatropha, survival, transplanting